Regional innovation systems of medical technology: A knowledge production function of cardiovascular research and funding in Europe - Rucha Vadia; Katharina Blankart (REGION, 2021)
We investigated the role of public funding in cardiovascular device innovation across 31 countries in Europe. We rely on the knowledge production function (KPF) framework that establishes the knowledge output of a region as a function of innovatory effort and other characteristics of that region. In a cross-sectional analysis, we investigated regional variation in knowledge production by the number of publications in cardiovascular device research obtained from the bibliometric data of the world's largest biomedical library, the US National Library of Medicine, 2014-2017. We mapped these publications to product categories of medical devices approved for cardiovascular diseases by the US Food and Drug Administration. Considering spatial correlation across regions of Europe in our estimates of the KPF, we investigated the impact of two types of public funding mechanisms: the volume of European Union (EU) Framework Programme (FP) 7 funding received by the innovating regions and that of its successor the EU Horizon 2020 funding. We obtained 123,487 cardiovascular device-related publications distributed across 1,051 (75% of total) regions (NUTS-3 level). Receiving public funding strongly contributes to a region's knowledge output. The estimated elasticities of innovatory effort by FP7 range between 0.36 and 0.40 while the estimated elasticities of Horizon 2020 range between 0.13 and 0.17. Estimated elasticities remain robust after controlling for country level fixed effects. When accounting for additional inputs to the KPF by private funding and health system related factors, the elasticity estimates for FP 7 and Horizon 2020 reduced, but remained significant. We documented spillover from neighboring regions, albeit at small scale. Our results conclude that innovatory efforts in the form of public research investments are effective for promoting innovation in the medical device industry at the regional level.
Keywords: R11; R12; O32; O52; 330; Innovation; Regional Innovation System; Medical Technology; Cardiovascular Devices; Innovatory Spillover; Spatial Spillover